Chidamide Combined With Doxorubicin Induced p53-Driven Cell Cycle Arrest and Cell Apoptosis Reverse Multidrug Resistance of Breast Cancer - Cao, Lixia; Zhao, Shaorong; Yang, Qianxi; Shi, Zhendong; Liu, Jingjing; Pan, Teng; Zhou, Dongdong; Zhang, Jin (Frontiers in Oncology, 2021)
The multidrug-resistant (MDR) phenotype is usually accompanied by an abnormal expression of histone deacetylase (HDAC). Given that HDAC is vital in chromatin remodeling and epigenetics, inhibiting the role of HDAC has become an important approach for tumor treatment. However, the effect of HDAC inhibitors on MDR breast cancer has not been elucidated. This study aim to demonstrate the potential of chidamide (CHI) combined with the chemotherapy drug doxorubicin (DOX) to overcome chemotherapeutic resistance of breast cancer in vitro and in vivo, laying the experimental foundation for the next clinical application. The results showed that, CHI combined with DOX showed significant cytotoxicity to MDR breast cancer cells in vitro and in vivo compared with the CHI monotherapy. The cell cycle distribution results showed that CHI caused G0/G1 cell cycle arrest and inhibited cell growth regardless of the addition of DOX. At the same time, Annexin V staining and TUNEL staining results showed that CHI enhanced the number of cell apoptosis in drug-resistant cells. The western blot analysis found that p53 was activated in the CHI-treated group and combined treatment group, and then the activated p53 up-regulated p21, apoptosis regulator recombinant protein (Puma) and pro-apoptotic protein Bax, down-regulated the apoptotic proteins Bcl-xL and Bcl-2, and activated the caspase cascade to induce apoptosis.